Women’s participation and the Incumbency Advantage in Slovak Cities: the Case Study of the Mayoral elections in Slovakia - Sloboda, Matúš (Socialiniai tyrimai, 2014)
The article focuses on the mayoral elections in all cities (138) in Slovakia. This analysis presents how the positions of mayors are distributed between men and women. Specific and detailed electoral data from the 2006 and 2010 mayoral elections allows for presuming whether the current distribution is caused by the electoral preferences of voters (demand) or by the supply of candidates. According to theoretical literature, mayors who are running for second term may have an advantage over their opponents. Data shows us how big this incumbency effect is in Slovak cities.
Keywords: incumbents; mayors; success rate; candidacy rate; women